Strength of Harian Metro tabloid as advertising media to the Al-Ikhsan business expansion in Bangsar / Muhammad Shukri Shukor (Faculty of Business Management, 2007)
Newspaper advertising is one of the promotion tool in the promotional mix. Lower advertising cost and mass audience is the advantages of newspaper advertising and it been preferred by developing company as their have small allocation in advertising. However, the measures of the newspaper advertising helping existing company to expand their business are yet unknown. This research is conducted to determine the strength of Harian Metro as advertising media to Al-Ikhsan business expansion. The research objective is to determine the strength of Harian Metro as a advertising media and to determine the relationship between the variable, which is right mental frame to process advertisement message, mass audience coverage, flexibility, ability to use detail copy and timeliness with the Harian Metro strength. The exploratory research and descriptive research was used in order to obtain the objectives. Sampling random sampling has been utilized with 50 respondents. Structured questionnaire was used as the survey instrument. By using the analysis generated by SPSS (Statistical Package for the Social Science), results are analyzed. All the result can can be determine under chapter four and for further explanation in under conclusion in chapter five.